Optimizing the Use of Recycled Materials in Environmentally Friendly Concrete Block Production - Amar, Tsulis Iq'bal Khairul; Magfirona, Alfia; Rosadi, Dheaulhaq; Putri, Nabila Faisa (Universitas Ibn Khaldun Bogor, 2025)
The construction industry significantly impacts the environment through resource consumption and carbon emissions. This study explores environmentally friendly concrete block production using recycled materials to address these challenges. By incorporating waste materials such as Styrofoam (X1), HVS paper (X2), and Onggok Aren fiber (X3), this study aimed to reduce landfill waste and lower carbon emissions. Our research shows that these materials can be effectively used in concrete block production, meeting required standards. However, high initial production costs remain a barrier. Effective cost modeling and optimization, using linear programming, showed that production costs for blocks made from Styrofoam (X1), HVS Paper (X2), and Onggok Aren Fiber (X3) could be significantly reduced. The optimized costs were Rp 1,804.26 for Styrofoam (X1), Rp 3,500 for HVS Paper (X2), and Rp 4,000 for Onggok Aren Fiber (X3) per block. By incorporating a 30% profit margin, the selling prices were set at Rp 2,345.54 for Styrofoam (X1), Rp 4,550 for HVS Paper (X2), and Rp 5,200 for Onggok Aren Fiber (X3). This approach ensures market competitiveness and sustainable profitability, promoting the use of alternative materials in construction and advancing environmental sustainability.